Estudio de factibilidad económica y financiera para la incorporación de las prestaciones del IESS en el centro de salud médikal de Guayaquil, como estrategia para el crecimiento del servicio a la colectividad - Cárdenas García, María Auxiliadora (2015)
Service delivery IESS, started as an initiative of the current national government, building on the need to provide decent care for members of IESS. In this context, this project was designed with the overall objective is to determine the economic viability of a proposed incorporation of services in the IESS health center "Medikal" city of Guayaquil as a strategy for the growth of service to the community . The scientific method in the development of research work, and the deductive method as a final step for hypothesis testing was used for this purpose. According to the results of the statistical formula applied to find the ideal sample is obtained as a result analyzed 384 people who are affiliated with the IESS in the city of Guayaquil………